The Role of Ultrasound in the Diagnosis and Management of Pediatric Abdominal Emergencies in Jakarta, Indonesia - Istiqomah Putri; Ratih Dwi Astuti (Phlox Institute: Indonesian Medical Research Organization, 2025)
Introduction: Pediatric abdominal emergencies demand swift and accurate diagnosis for optimal management. In resource-constrained settings, point-of-care ultrasound (POCUS) has emerged as a valuable tool. This study aimed to evaluate the utility of ultrasound in diagnosing and managing pediatric abdominal emergencies in Jakarta, Indonesia. Methods: A retrospective review of pediatric patients (age ≤ 18 years) presenting with acute abdominal pain to a tertiary care hospital in Jakarta from 2018 to 2023 was conducted. Data collected included demographics, clinical presentation, ultrasound findings, final diagnosis, and management decisions. Sensitivity, specificity, positive predictive value (PPV), and negative predictive value (NPV) of ultrasound for various abdominal emergencies were calculated. Results: A total of 543 patients met the inclusion criteria. The most common diagnoses were appendicitis (n=187, 34.4%), intussusception (n=82, 15.1%), and gastroenteritis (n=75, 13.8%). Ultrasound demonstrated high sensitivity and specificity for diagnosing appendicitis (92% and 88%, respectively), intussusception (95% and 90%), and free fluid in the abdomen (98% and 94%). POCUS influenced management decisions in 68% of cases, including expediting surgery or avoiding unnecessary interventions. Conclusion: Ultrasound is a valuable tool for the diagnosis and management of pediatric abdominal emergencies in Jakarta. Its high sensitivity and specificity, coupled with its point-of-care availability, make it particularly useful in resource-limited settings.